Sialic Acid Transporter NanT Participates in Tannerella forsythia Biofilm Formation and Survival on Epithelial Cells - Honma, Kiyonobu (Microb Pathog, 2015)
Tannerella forsythia is a periodontal pathogen implicated in periodontitis. This gram-negative pathogen depends on exogenous peptidoglycan amino sugar N-acetylmuramic acid (NAM) for growth. In the biofilm state the bacterium can utilize sialic acid (Neu5Ac) instead of NAM to sustain its growth. Thus, the sialic acid utilization system of the bacterium plays a critical role in the growth and survival of the organism in the absence of NAM. We sought the function of a T. forsythia gene annotated as nanT coding for an inner-membrane sugar transporter located on a sialic acid utilization genetic cluster. To determine the function of this putative sialic acid transporter, an isogenic nanT-deletion mutant generated by allelic replacement strategy was evaluated for biofilm formation on NAM or Neu5Ac, and survival on KB epithelial cells. Moreover, since T. forsythia forms synergistic biofilms with Fusobacterium nucleatum, co-biofilm formation activity in mixed culture and sialic acid uptake in culture were also assessed. The data showed that the nanT-inactivated mutant of T. forsythia was attenuated in its ability to uptake sialic acid. The mutant formed weaker biofilms compared to the wild-type strain in the presence of sialic acid and as co-biofilms with F. nucleatum. Moreover, compared to the wild-type T. forsythia nanT -inactivated mutant showed reduced survival when incubated on KB epithelial cells. Taken together, the data presented here demonstrate that NanT-mediated sialic transportation is essential for sialic acid utilization during biofilm growth and survival of the organism on epithelial cells and implies sialic acid might be key for its survival both in subgingival biofilms and during infection of human epithelial cells in vivo.